BITCOIN DALAM PANDANGAN CENDIKIAWAN MUSLIM KLASIK DAN KONTEMPORER - Munawir (AL-RASYAD: JURNAL HUKUM DAN ETIKA BISNIS SYARIAH, 2023)
This article examines the views of Muslim scholars regarding bitcoin. The main problem examined in this article is the views of classical and contemporary scholars regarding the use of bitcoin. The author uses the literature study method with primary and secondary references from books, scientific articles, theses, dissertations, encyclopedias, internet and other sources. After carrying out a series of rigorous and in-depth research systems, the authors found that the existence of bitcoin as a virtual currency is considered valid, legal, or permitted under conditions, that is, if it is recognized by the state. This is because the rights and obligations to manage iqtishadiyah, including the issuance of a new currency, are under the authority of the state. In this case, bitcoin is not issued by the state and is not recognized by Bank Indonesia, so bitcoin is a currency that is considered not legal in Indonesia. The concept of bitcoin according to classical and contemporary scholars is basically the same as money in general. Actually bitcoin is a digital currency that can be used by developed countries. He is very influential in the traffic of the modern economy. As for the law, the use of bitcoins as currency or business transactions is haram li ghairihi, because the prohibition is caused by others, not the bitcoin substance itself. And also because of its uncertain nature, it is possible to cause chaos and harm many people.